Features of legal regulation of tax incentives for small business in Post-Socialist Countries - Vakaryuk, Lyudmyla; Babin, Igor (Silesian Journal of Legal Studies, 2018)
Small businesses are one of the main factors of political and social stability of society and national economy in the modern European states. However, small businesses are vulnerable to a number of factors (inflation, expensive costs of credits, instability and complexity of tax law, burdens of public administration and permitting system) and require government support. In the world practice, the state support of small businesses uses a wide range of tools, including targeted government funding, assistance in formation of seed capital, preferential loans, preferential taxation, leasing, franchising, protectionism in investment and export policy, priority subsidies or information. The most effective tools of the state support are financial methods, especially fiscal methods, carried out directly through the tax system. In the following paper, experience in application of instruments of tax incitement in the tax systems of the post-socialist countries has been analysed while three trends of use of instruments of tax regulation have been revealed. The first one is avoiding the use of special tax regimes and a significant reduction of tax preferences. The second one represents limited use of special tax regimes and introduction of the complex of incentive tax preferences aimed at reducing of the tax load at tax system, creating new work places and encouraging research, investment and innovation activities. The third one means wide use of special tax regimes, joined with provision for small business tax preferences. Finally, recommendations about the adaptation of certain foreign tax technologies and tools to the national tax legislation and practice have been proved.
Keywords: Tax Law; Tax System; Preferential Taxation; Special Tax Regimes; Small Businesses; Postsocialist Countries; Ukraine